THE RESEARCH OF AGIOGRAPHIC WORKS IN TRANSLATION STUDY - Tuxtasinova, Nigina (Журнал иностранных языков и лингвистики, 2021)
This article is devoted to research of agiographic works in translation study. The study showed that foreign scientists have done a lot of research in the field of hagiographic works. Despite the presence of huge monographic works and researches on the study of hagiographic works in the Uzbek linguistics of literary criticism, it should be noted the first steps taken in Uzbek translation studies, which is the demand of the time.